Lanczos generator in Gödel geometry - Ahsan, Z.; Caltenco, J. H.; Linares-y-M, R.; López-Bonill, J. (Communications in Physics, 2012)
We exhibit three ways to obtain a Lanczos spintensor for the Gödel cosmological model. In particular, a symmetric tensor of rank two is constructed which satisfies the wave equation and generates a Lanczos potential.